Comparing Land Reform and Land Markets in Colombia : Impacts on Equity and Efficiency - Deininger, Klaus (World Bank, Washington, DC, 2013)
Based on a large survey to compare the effectiveness of land markets and land reform in Colombia, the authors find that rental and sales markets were more effective in transferring land to poor but productive producers than was administrative land reform. The fact that land transactions were all of a short-term nature and that little land was transferred from very large to small land owners or the landless suggests that there may be scope for policies both to improve the functioning of land markets and to facilitate greater land access by the most disadvantaged. Analysis of the factors associated with success in a sample of land transfers from large to small producers helps to identify key elements for policies in both respects.